2004
DOI: 10.1242/jcs.01384
|View full text |Cite
|
Sign up to set email alerts
|

p73 competes with co-activators and recruits histone deacetylase to NF-Y in the repression of PDGF β-receptor

Abstract: We investigated mechanisms of the p73α-mediated repression of the platelet-derived growth factor β-receptor (PDGFRB) promoter caused by its interaction with NF-Y. Treatment of cells with the histone deacetylase (HDAC) inhibitor, Trichostatin A, increases PDGFRB promoter activity through the CCAAT motif and counteracts the repression caused by p73α. Activation of the PDGFRB promoter by the co-activator p300 also occurs through the CCAAT motif. Expression of p73α counteracts both p300- and P/CAF-mediated activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 25 publications
5
26
0
Order By: Relevance
“…HDAC1 has been reported to interact with various transcription factors to repress specific genes. NF-Y has been shown to be associated with HDAC1 and the association is mediated by other proteins such as p73 (45). In this study, we showed that the interaction between HDAC1 and NF-Y is enhanced by RFP in transformed cells.…”
Section: Discussionsupporting
confidence: 50%
“…HDAC1 has been reported to interact with various transcription factors to repress specific genes. NF-Y has been shown to be associated with HDAC1 and the association is mediated by other proteins such as p73 (45). In this study, we showed that the interaction between HDAC1 and NF-Y is enhanced by RFP in transformed cells.…”
Section: Discussionsupporting
confidence: 50%
“…Several transcription factors (TFs) are known to activate or repress Pdgfrb in cell culture systems; however, the biological function of Pdgfrb regulation by these TFs in vivo remains elusive (Ballagi et al, 1995;Uramoto et al, 2004;Jin et al, 2008;Weissmueller et al, 2014). In the present study, we show Koss et al, 2012) and the osteoblast-related gene Osx (Sp7 -Mouse Genome Informatics) (Gordon et al, 2010).…”
Section: Discussionmentioning
confidence: 59%
“…In nonstressed cells, NF-Y is present on the Grp78 promoter and may play a role in suppressing its activity through interactions with transcriptional repressors (44,53). The presence of a high-affinity NF-Y binding site has previously been shown to be necessary for ATF6-mediated induction of the Grp78 promoter (24), and it may also attract other coactivators and chromatin modifiers to the promoter, resulting in activation (5).…”
Section: Discussionmentioning
confidence: 99%